2016
DOI: 10.1590/s1980-5764-2016dn1004008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive performance on quality of life in individuals with Parkinson's disease

Abstract: BackgroundEvidence points to the occurrence of cognitive impairment in all stages of PD, constituting a frequent and debilitating symptom, due to high impact on quality of life and mortality of patients.ObjectiveTo correlate cognitive performance with quality of life in PD.MethodsThe sample was drawn from a Movement Disorders Clinic of a reference hospital in Porto Alegre. Inclusion criteria were: PD diagnosis, according to the United Kingdom Parkinson's Disease Society Brain Bank criteria for idiopathic PD (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
(41 reference statements)
1
12
1
2
Order By: Relevance
“…Changes in the central nervous system resulting from Parkinson’s disease (PD) lead to the manifestation of non-motor symptoms, such as cognitive deficits and increased depressive symptoms [ 1 , 2 ]. The severity of non-motor and motor symptoms, in turn, is causally related to deficits in quality of life (QoL) [ 3 , 4 ]. Furthermore, some studies show the influence of sedentary time on factors associated with quality of life in people with PD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the central nervous system resulting from Parkinson’s disease (PD) lead to the manifestation of non-motor symptoms, such as cognitive deficits and increased depressive symptoms [ 1 , 2 ]. The severity of non-motor and motor symptoms, in turn, is causally related to deficits in quality of life (QoL) [ 3 , 4 ]. Furthermore, some studies show the influence of sedentary time on factors associated with quality of life in people with PD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a mechanistic standpoint, enhanced cognitive function implies mitigating not just movement disorders but also non-motor symptoms including autonomic dysfunction, sleep disorders, and pain [ 4 , 5 , 14 ]. Although positive motor and clinical adaptation using Nordic walking in patients with PD have been shown [ 10 , 12 , 15 , 16 ], to the best of our knowledge no data have been reported about the effects of Nordic walking in comparison to a free walking training program on QoL and non-motor symptoms in individuals with PD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in their population-based study, Schrag, Jahanshahi, and Quinn (2000) identified a significant correlation between results on the Mini-Mental State Exam (Folstein, Robins, & Helzer, 1983) and the Parkinson's Disease Questionairre-39 (a PD specific measurement of quality of life; Peto, Jenkinson, & Fitzpatrick, 1998). A similar relationship between cognitive decline and quality of life has also been replicated more recently by Olchik, Ayres, Ghisi, Schuh, and Rieder (2016). In addition, the presence of significant cognitive deficits has been linked to greater caregiver distress or burden (Aarsland, Larsen, Karlsen, Lim, & Tandberg, 1999;Lawson et al, 2016;Leroi, McDonald, Pantula, & Harbishettar, 2012) and higher incidence of nursing home admission (Aarsland, Larsen, Tandberg, & Laake, 2000).…”
Section: Cognitive Impairment In Parkinson's Diseasementioning
confidence: 83%
“…A prevalência de déficit cognitivo leve em estágios iniciais é de 15-25% e aproximadamente 50% das PDP desenvolvem demência nos primeiros 10 anos do curso da doença (OLCHIK et al, 2016).…”
Section: Sintomasunclassified
“…Alguns fatores contribuem para que o indivíduo tenha maior propensão a desenvolver déficits cognitivos, são eles: idade avançada, baixa escolaridade, rigidez, instabilidade postural, distúrbios do sono REM, alucinações e substância branca afetada (OLCHIK et al, 2016).…”
Section: Sintomasunclassified